A Novel Tool for the Evaluation of Residency Training: Scale Development and Validation - Nazan Karaoğlu; Ümmü Doğan; Aşir Genç; Nur Demirbaş; Fatih Yılmaz; Hatice Küçükceran; Fatma Gökşin Cihan; Ümran Münire Kahraman (İstanbul Medical Journal)
Introduction: The purpose of medical specialty training is to provide the physician with sufficient knowledge, skills, attitudes, and qualifications in the chosen field of medicine. In medical training, communication and social opportunities are crucial as well as appropriate goals, programs, and learning environments. The purpose of this paper is to develop a valid and reliable measurement tool to evaluate the compliance of this training with the standards. Methods: In this survey-type research, in line with the literature, a draft scale to evaluate the training in both the department and the institution consisting of 49 items, was created. Results: The study involved 497 residents from family medicine residency programs across Türkiye. The exploratory factor analysis revealed that the Scale for Department Evaluation of Medical Specialty Training had four factors whereas the Scale for Institution Evaluation of Medical Specialty Training had three factors. The factorial structures of both scales were confirmed by confirmatory factor analysis. The Cronbach’s alpha values were 0.941 and 0.928, respectively. Moreover, both scales explain a high amount of total variance. Conclusion: The Department Evaluation Scale for Medical Specialty Training, consisting of 25 items and four factors, and the Institution Evaluation Scale for Medical Specialty Training consisting of 20 items and three factors are valid and reliable tools to study medical specialty training.